IMPLEMENTASI GERAKAN 1821 DALAM MENINGKATKAN PRESTASI SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Rokim Rokim (Akademika, 2019)
There is a reality showing the influence of gadgets on the development of children today. They are increasingly selfish, difficult to control and easily affected by other negative impacts. There are many students preferring to play gadgets rather than studying, reading or writing. Therefore, it is necessary to consider the so-called 1821 Movement implementation in improving student achievement. The 1821 Movement is a new study program promoted by the Regent of Lamongan in which at 18.00-21.00 students are encouraged not to pay more attention to the gadgets and and the time is solely used for learning. In this study, the writer is intended to know the implementation of the 1821 Movement, the supporting and inhibiting factors and the ways of overcoming the inhibiting ones. This study could be concluded that the implementation of the 1821 Movement has contributed to a significant increase in student achievement. Broadly speaking, this could be seen from a number of aspects: students are considerably prepared to take lessons when classes begin, achievments increase, the presence of professional teachers are one of the factors supporting the 1821 Movement.